Implications of GABAergic Neurotransmission in Alzheimer’s Disease - Li, Yanfang; Sun, Hao; Chen, Zhicai; Xu, Huaxi; Bu, Guojun; Zheng, Hui (Frontiers in Aging Neuroscience, 2016)
Alzheimer’s disease (AD) is characterized pathologically by the deposition of -amyloid peptides (A) and the accumulation of neurofibrillary tangles (NFTs) composed of hyper-phosphorylated tau. Regardless of the pathological hallmarks, synaptic dysfunction is widely accepted as a causal event in AD. Of the two major types of synapses in the CNS: glutamatergic and GABAergic, which provide excitatory and inhibitory outputs respectively, abundant data implicate an impaired glutamatergic system during disease progression. However, emerging evidence supports the notion that disrupted default neuronal network underlies impaired memory, and that alterations of GABAergic circuits, either plays a primary role or as a compensatory response to excitotoxicity, may also contribute to AD by disrupting the overall network function. The goal of this review is to provide an overview of the involvement of A, tau and apoE4, the major genetic risk factor in late-onset AD, in GABAergic neurotransmission and the potential of modulating the GABAergic function as AD therapy.